Anticancer potential of Damnacanthal and Nordamnacanthal from Morinda elliptica roots on T-lymphoblastic leukemia cells - Saiful Yazan, Latifah; Gopalsamy, Banulata; Abdul Rahim, Raha; Ali, Abdul Manaf; Lajis, Nordin (Multidisciplinary Digital Publishing Institute, 2021)
Background: This study reports on the cytotoxic properties of nordamnacanthal and damnacanthal, isolated from roots of Morinda elliptica on T-lymphoblastic leukaemia (CEM-SS) cell lines. Methods: MTT assay, DNA fragmentation, ELISA and cell cycle analysis were carried out. Results: Nordamnacanthal and damnacanthal at IC50 values of 1.7 μg/mL and10 μg/mL, respectively. At the molecular level, these compounds caused internucleosomal DNA cleavage producing multiple 180–200 bp fragments that are visible as a “ladder” on the agarose gel. This was due to the activation of the Mg2+/Ca2+-dependent endonuclease. The induction of apoptosis by nordamnacanthal was different from the one induced by damnacanthal, in a way that it occurs independently of ongoing transcription process. Nevertheless, in both cases, the process of dephosphorylation of protein phosphates 1 and 2A, the ongoing protein synthesis and the elevations of the cytosolic Ca2+ concentration were not needed for apoptosis to take place. Nordamnacanthal was found to have a cytotoxic effect by inducing apoptosis, while damnacanthal caused arrest at the G0/G1 phase of the cell cycle. Conclusion: Damnacanthal and nordamnacanthal have anticancer properties, and could act as potential treatment for T-lymphoblastic leukemia.